The 2012 Wildfire Evacuation Experiences of Dene Tha' First Nation ... - Mottershead, Kyla D (University of Alberta Library, 2017)
Almost every year, First Nations are evacuated in Canada due to wildfire proximity and smoke. The remote locations, unique sociocultural characteristics, and limited emergency management resources and infrastructure of many First Nations can present challenges for residents and evacuation organizers. In addition, the evacuation process itself is administratively and operationally complex and can result in social, psychological, health, and economic implications for First Nations and their individual members. However, little research has sought to examine how these communities are affected by wildfire evacuations. No research has examined how a First Nations community experiences a community-wide mandatory evacuation due entirely to wildfire smoke, despite a large proportion of smoke evacuations involving First Nations. This study addresses this gap in the hazards literature and provides improved understanding of the entire evacuation process from the perspective of community members. Specifically, this study ...